Strategi Pemasaran Digital Produk Halal Dalam Meningkatkan Branding Bisnis Syariah - Natsir, Imron; Siregar, Sulaiman Efendi; Triastuti, Eny; Parmini; Yuliastuti, Ratna (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study is to determine the effectiveness of digital marketing strategies for halal products in improving branding of sharia businesses. This research approach collects data through literature studies, which involve reading literature from various sources including books, articles, journals and reports using qualitative and deductive approaches. The findings in this study are that digital marketing strategies are an important element in improving branding of sharia businesses and halal products. By utilizing search engine optimization (SEO), social media marketing, influencer marketing, storytelling, e-commerce and marketplace optimization, and email marketing, sharia businesses can build strong branding, increase customer trust, and expand market reach globally. Through the implementation of appropriate and consistent digital strategies, sharia businesses can compete in a wider market, reach more Muslim customers, and have a positive impact on the development of the global halal industry.